The Variety of Counseling Skill Supervision as a Learning Process - Desriani Rahmania; Lucky Nindi Riandika Marfu’i; Rike Ulandari; Desriani Rahmania; Lucky Nindi Riandika Marfu’i (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2025)
An absence of adequate counseling skill supervision as a learning process leads to low self-efficacy, such as avoidance and high levels of anxiety in practice sessions. It can also negatively affect students’ academic progress and their motivation to continue in the training program. Counseling skill supervision must consider supervisees’ specific needs. On the other hand, the supervisor tends to use the same supervision methods for different needs due to a limited understanding of the variety and effectiveness of different counseling skill supervision approaches, this research aims to determine the variety of counseling skill supervision using an integrative literature review. The result has shown that most supervisory processes use the developmental models. The result indicated that the variations incorporating AI, AR, VR, and addressed specific supervisory needs. First, Communication barriers were managed through supervisees’ submission of pre and post-project recordings, enhancing evidence-based communication across competence levels. Second, personal bias was reduced through AI-generated or other technology support structure feedback for beginner supervisees’ challenges. Third, supervisory relationship challenges at the intermediate level were supported by promoting autonomy and structured, evidence-based reflection through an integrative approach.